2016
DOI: 10.1093/gbe/evv263
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Natural Hybridization in Brazilian Wild Lineages ofSaccharomyces cerevisiae

Abstract: The natural biology of Saccharomyces cerevisiae, the best known unicellular model eukaryote, remains poorly documented and understood although recent progress has started to change this situation. Studies carried out recently in the Northern Hemisphere revealed the existence of wild populations associated with oak trees in North America, Asia, and in the Mediterranean region. However, in spite of these advances, the global distribution of natural populations of S. cerevisiae, especially in regions were oaks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 59 publications
8
107
0
2
Order By: Relevance
“…(2016) recently reported novel S. cerevisiae lineages in Brazil that are related to Japanese and North American lineages, but the Brazilian populations also contain signals for mating and introgression with the wine/European group, as well as hybridisation and introgression with American S. paradoxus. This hybridisation and subsequent introgression conceivably provided novel genetic combinations better adapted to inhabit Brazilian native biomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2016) recently reported novel S. cerevisiae lineages in Brazil that are related to Japanese and North American lineages, but the Brazilian populations also contain signals for mating and introgression with the wine/European group, as well as hybridisation and introgression with American S. paradoxus. This hybridisation and subsequent introgression conceivably provided novel genetic combinations better adapted to inhabit Brazilian native biomes.…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no estimations regarding the timing of either the Brazil or cocoa and coffee strain movements (Barbosa et al . 2016; Ludlow et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even under controlled process conditions, in which the domesticated yeasts are more prevalent, recent comparative genomic studies have demonstrated cases of spoilage in ethanol plants where native yeast strains were found to indeed overlap those inoculated ones. These wild yeasts can be found in different matrices, from wine making-related environments to tree barks, fruits and even seawater (Duina et al, 2014;Barbosa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%